Effect of frozen gloves on chemotherapy-induced neurotoxicity in breast cancer patients: a systematic review and meta-analysis - Wu, Hongting; Jin, Ying; Song, Jiaqing; Gao, Xiufei (Frontiers in Oncology, 2024)
Background: Chemotherapy-induced peripheral neurotoxicity (CIPN) is a dose-limiting side effect observed in breast cancer patients. Its primary clinical manifestations include limb numbness, tingling sensations, hypoesthesia, or paresthesia. In severe instances, some patients may also encounter muscle cramps, weakness, and pain, leading to potential paralysis. The onset of CIPN significantly impacts the quality of life for cancer patients. Hence, it is imperative to explore preventive strategies for managing CIPN.We searched for relevant randomized controlled trials (RCTs) and non-randomized controlled trials (non-RCTs) in several databases. The primary outcome measures encompassed the Patient Neurotoxicity Questionnaire (PNQ), the Functional Assessment of Cancer Therapy-Taxane (FACT-Taxane), and the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE). Secondary outcomes aimed to evaluate the quality of life and the tolerability of ice gloves. Meta-analysis was conducted using RevMan 5.3 software to determine the relative risk ratio (RR) and 95% confidence interval (CI).We conducted an analysis involving 372 patients across seven trials. In our meta-analysis, the use of ice gloves demonstrated non-significant results in reducing the incidence of both motor and sensory neuropathy, as assessed through CTCAE (sensory: RR: 0.94; 95% CI: 0.85 to 1.02; P = 0.15; motor: RR: 1.04; 95% CI: 0.88 to 1.22; P = 0.64). Similarly, when evaluated using the PNQ, there was no significant reduction observed in the incidence of sensory and motor neuropathy (sensory: RR: 0.49; 95% CI: 0.20 to 1.20; P = 0.12; motor: RR: 0.71; 95% CI: 0.26 to 1.99; P = 0.52). Consistently, our conclusions remained unchanged when employing the FACT-Taxane assessment. Regarding the evaluation of the quality of life, our observations suggested a potential improvement with the use of ice gloves, and participants exhibited moderate tolerance towards them.Ice gloves are a reasonable option for the treatment of CIPN in patients undergoing chemotherapy for breast cancer. However, the effectiveness of ice gloves in combating CIPN remains inconclusive at this time due to the low quality and limited number of clinical trials on this topic.